Market performance of sharia-compliant companies in Indonesia: relevance of earnings-management, leverage, and corporate - Yunice Karina Tumewang (Faculty of Economics, Universitas Islam Indonesia, 2017)
This study aims to explore the factors that influence the Islamic bank profitability. The profitability rate or Return on Asset (ROA) is utilized as dependent variable whereas internal financial factor (financial ratio indicator) and external factor (economic indicator) are adopted as independent variable. This study focus on social funds such as qard and ZIS contract. This study applies qualitative description with using time series data from March 2010 to September 2014. Moreover, Panel regression model is employed, MWD test and classical assumption test. This analysis finds that, firstly, financial ration and CAR has positive and not significant relationship although equity based financing has significant and positive relationship then in economic indicator results GDP growth and inflation has positively not significant. Furthermore, social funds indicator such in qard contract has positive and significant relationship to ROA or profitability rate. However, the second regression result that utilizes ZIS variable finds that all variables do not have significant relationship excluding GDP growth.